Zimbabwe's agricultural revolution - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Zimbabwe's agricultural revolution edited by Mandivamba Rukuni and Carl Eicher 1994 418pp price UKL25.00 US$45.00 ISBN 0 90830738 1